Efficacy and Safety of SBRT Combined With Camrelizumab and Apatinib in HCC Patients With PVTT: Study Protocol of a Randomized Controlled Trial - Hu, Yue; Qin, Tingting; Li, Shuang; Zhang, Tao; Xue, Jun (Frontiers in Oncology, 2020)
Background Hepatocellular carcinoma (HCC) patients with portal vein tumor thrombosis (PVTT) has poor prognosis. Sorafenib/lenvatinib is recommended as the first-line therapy in these patients currently, with unsatisfactory response and survival benefit reported. Radiotherapy (RT) is increasingly utilized in advanced HCC and is considered an alternative option for HCC patients with PVTT. Combined treatment of RT and locoregional treatments such as transarterial chemoembolization shows promising results. However, the efficacy and safety for combined treatment of RT and systemic therapy have not been reported and thus warrant further studies. This prospective clinic trial aims at evaluating the efficacy and safety of stereotactic body RT (SBRT) combined with camrelizumab and apatinib in HCC patients with PVTT. Methods This multicenter, open-label, randomized controlled trial will enroll 264 HCC patients with PVTT who have not received systemic therapy previously. Stratification of patients will be based on the presence or absence of extrahepatic metastasis and level of AFP (AFP ≥ 400 or <400 ng/mL) and randomly assigned 1:1 to study and control groups. Patients in study group will receive SBRT (95% PTV 36–40 Gy/6–8 Gy), camrelizumab (200 mg every 3 weeks), and apatinib (250 mg every day), and patients in control group will receive camrelizumab (200 mg every 2 weeks) and apatinib (250 mg every day). Patients will be followed up for 1.5 to 3.5 years since the start of therapy. We will use overall survival as the primary endpoint and progression-free survival, objective response rate, disease control rate, adverse events, and quality of life as the secondary endpoints. Discussion This study will be the first randomized controlled trial to assess the efficacy and safety of SBRT combined with camrelizumab and apatinib for HCC patients with PVTT. The results may help establish a new standard first-line therapy for these patients. Trial Registration Chinese Clinical Trial Registration No. ChiCTR1900027102. Date of Registration October 31, 2019.